KARAKTERISTIK RAW MATERIAL EPOXY RESIN TIPE BQTN-EX 157 YANG DIGUNAKAN SEBAGAI MATRIK PADA KOMPOSIT (THE CHARACTERISTICS OF RAW MATERIAL BQTN-EX 157 EPOXY RESIN USED AS COMPOSITES MATRIX) - Sri Rahayu; Mabe Siahaan (National Institute of Aeronautics and Space - LAPAN, 2017)
The objective of the research is to characterize resin raw material used as matrix in composite. Resins are rigid or semi-rigid polymer materials at room temperature, whereas epoxy resins are a class of organic chemical bonding systems used in special coating or adhesive preparations. This study reports the composition effect of BQTN-EX 157 epoxy resin with its hardener on mechanical, physical, and chemical properties. For the purpose, samples were prepared by varying the composition of the mixture (volume fraction) between epoxy resins and hardener ie 2: 1/4, 2: 1/2, 2: 3/4, and 2: 1. The mixture was molded into plate sheets for 7 days, then were formed into test specimens. The specimens were tested for their ultimate tensile strength (σu,) with Universal Testing Machines (UTM) AND RTF-2410 series, their densities (ρ) with FH-MD200 series densitometer, and their molecular group with IR Prestige-21 series FTIR. Results show that the lowest and highest mean tensile strength values of 16.4872 and 57.9254 MPa were produced in the mixed compositions of 2: 1/4 and 2: 1, the lowest mean density was 1.1065 g/cc and the highest was 1.1430 g/cc on a mixture of 2: 1 and 2: 1/4 compositions. Furthermore, the absorption frequency value occurs at 1050 -1700 cm-1 and in this frequency region the lowest and highest formation of peak C-O and C=C occurs. Thus it can be concluded that if the amount of volume fraction of hardener more mixed with epoxy resin will increase ultimate tensile strength; decreases density; and resulting into the formation of C-O and C=C compounds. ABSTRAKTujuan dari penelitian adalah mendapatkan karakterisasi raw material resin yang digunakan sebagai matrik pada komposit. Resin adalah material polimer yang kaku atau semi kaku pada suhu kamar, sedangkan epoxy resin adalah kelas sistem ikatan kimia organik yang digunakan dalam preparat lapisan khusus atau perekat. Penelitian ini melaporkan pengaruh komposisi resin epoxy BQTN-EX 157 dengan hardener terhadap sifat mekanik, fisis, dan kimia. Untuk itu, sampel dibuat dengan variasi komposisi campuran (fraksi volume) antara epoxy resin dengan hardener 2:1/4, 2:1/2, 2:3/4, dan 2:1. Kemudian campuran dicetak menjadi lembaran plat selama 7 hari, setelah itu lembaran plat dibentuk menjadi spesimen uji. Selanjutnya spesimen diuji kuat tariknya (σu) dengan Universal Testing Machines (UTM) seri AND RTF-2410, densitasnya (ρ) dengan densitometer seri FH-MD200, dan group molekulernya dengan FTIR seri IRPrestige-21. Secara berturut-turut, nilai rata-rata kuat tarik terendah dan tertinggi adalah 16.4872 dan 57.9254 MPa yang dihasilkan pada komposisi campuran 2 : 1/4 dan 2 : 1, nilai rata-rata densitas terendah 1.1065 g/cc dan tertinggi 1.1430 g/cc pada komposisi campuran 2 :1 dan 2 : 1/4. Selanjutnya nilai frekuensi penyerapan terjadi pada 1050 1700 cm-1 dan pada daerah frekuensi ini terjadi pembentukan peak C-O dan C=C terendah dan tertinggi. Dengan demikian dapat disimpulkan bahwa jika jumlah fraksi volume dari hardener semakin banyak dicampur dengan resin epoxy akan meningkatkan kuat tarik; menurunkan densitas, dan menghasilkan pembentukan senyawa C-O dan C=C.